EFFECT OF SOME NON-GENETIC FACTORS ON CHANGE OF SEX RATIO IN THE AWASSI SHEEP BREED - Isa Yilmaz; Mehmet Sari; Kadir Önk; Ali Kaygisiz (Journal of Animal and Plant Sciences, 2025)
This study investigated the influence of environmental and maternal factors on the sex ratio of Awassi lambs reared at the Ceylanpinar State Production Farm (CSPF) in Türkiye. Lambing data from 2004 to 2011 were analyzed using factorial ANOVA (FANOVA) and chi-square tests to evaluate the effects of lambing year and ewe age. While the effect of lambing year on sex ratio was only marginally significant (p<0.10), a statistically significant relationship was found between lamb sex and lambing year (p<0.01), indicating temporal variation in sex ratio. In particular, a female sex ratio of 54.41%, 55.58% and 52.21% was observed in the drought years 2006, 2007 and 2008, respectively. These patterns suggest that environmental stressors such as drought and reduced forage availability may exert directional pressure in favor of female offspring under suboptimal conditions. The results are consistent with the Trivers-Willard hypothesis and support the notion that maternal condition may influence sex allocation in a context-dependent manner.
Keywords: Awassi Sheep; Lamb; Sex ratio; Maternal investment; Trivers–Willard hypothesis